Racism and Beauty Standards in Indonesia: Audre Lorde's View - Dewanti, Erisa Nada; Fauzi, Ahmad; Tuzaroh, Fatimah (Journal of Feminism and Gender Studies, 2025)
Beauty standards are the result of social control influenced by the media. The standard of beauty circulating in Indonesia is that women are considered beautiful if they have white skin. This is contrary to the wealth of Indonesia which has various types of skin color. As a result, beauty standards give rise to racism in the form of physical insults, especially skin color for women with dark or black skin. This research aims to examine racism in Audre Lorde's "Sister Outsider" with the issue of racism in Indonesia which arises due to beauty standards. The research method used is descriptive qualitative with data collection via internet searching and analyzed using discourse analysis. The result from this research include; 1. Racism arises because of a sense of superiority, 2. The standard of beauty in Indonesia is women with white skin, 3. True beauty is seen from the heart and morals. Being a woman does not always mean following beauty standards, but we can create our own version of beauty standards by loving, appreciating and caring for ourselves more through various positive activities that can improve our quality.